An Appraisal of Career Development among Female Professionals in the Nigerian Construction Industry (Global Journals of Research in Engineering, 2012)
There are limited empirical studies on factors preventing female professionals from working in the construction industry. Thus, this study becomes imperative with a view to identifying and assessing the career development programmes and strategies as well as the impediments relating to career development programmes. The primary data consists of survey questionnaire, drawn on the basis of the identified career development programmes and the impediments relating to career development programs on existing literature. Random sampling technique was employed in the administration of the questionnaire to professional in consulting and contracting firms within the built environment in Lagos metropolis, Nigeria. The data were analyzed using statistical methods of average, percentage, mean score (MS), Kruskal Wallis H test and Mann Whitney#x2019;s U test. The results of the mean score ranking indicate factors influencing female professionals#x2019; participation in construction industry. However, the result of the Kruskal Wallis H test and Mann Whitney U test support null hypothesis. Also the result of the mean scores further show career development programmes and strategies, the result of Kruskal Wallis H test and Mann Whitney U test were significant. Finally, the result shows the impediments to career development programs and strategies. The study revealed career development programmes and strategies, this would provide necessary information to the government, stakeholders and employers of labour in the construction industry to ameliorate skilled shortages, enhance productivity and performance in the construction sector.
Keywords: Female professional; Career development; Construction industry; Nigeria; Strategies; Impediments